MANAJEMEN DAYA TARIK WISATA DI DESA BARAKATI KABUPATEN GORONTALO - Ainun Makrun; Anggraeni M.S Lagalo; Desrika Talib (Tulisan Ilmiah Pariwisata (TULIP), 2024)
This research was conducted because it concerns aspects of the management of Taluhu Barakati and Snake Cave tourism thus it can be maintained sustainably, and receive serious attention from stakeholders. This research aims to identify the management of tourism attractions that have become the village's main tourist attraction. This research used a descriptive qualitative approach carried out at the Taluhu Barakati and Snake Cave tourism sites, by interviewing 18 informants who were trusted to know the problems of managing tourism attractions from various sectors, namely the government, tourists and the community around the research location. Data collection techniques, namely observation, documentation and interviews, were carried out to complete the primary data. The results showed management in Barakati Village is very lacking at the planning stage, governance, management activities, and monitoring efforts from tourist attraction stakeholders are not optimal due to the inability of the management organization structure which is not orderly. Therefore at the planning and movement stages of managing tourism attractions, it is necessary to fulfill the planning conceptualization